To the origin of Lake Baikal endemic gammarid radiations, with description of two new Eulimnogammarus spp. - Moskalenko, Victoria N.; Neretina, Tatiana V.; Yampolsky, Lev Y. (Zootaxa, 2020)
Extraordinarily diverse morphologically and ecologically, Lake Baikal’s two endemic gammaroidean amphipod clades are both firmly placed within the paraphyletic genus Gammarus, based both on morphological and molecular characters. However, the exact placement of the two Baikal clades remains elusive, making reconstruction of the ancestral state of Baikal endemic radiation difficult. We sequenced 2 mitochondrial and 3 nuclear genes from several species of each of the two clades aiming to represent early branches of the radiation. We also describe two new species of Baikal gammarids, Eulimnogammarus etingovae sp. nov. and Eulimnogammarus tchernykhi sp. nov., with some morphology suggestive of basal position within the radiation. We confirm the two previously demonstrated Baikal clades, but cannot unequivocally support any of the previous hypotheses about affinities of the two Baikal clades within palearctic Gammarus species. Rather, it appears that the two Baikal endemic radiations separated from the rest of freshwater Palearctic forms early and rapidly, probably as part of gammarid diversification during colonization of fresh waters in Middle Eocene.